STRATEGI MARKETING POLITIK PARTAI DEMOKRASI INDONESIA PERJUANGAN DALAM PEMILU LEGISLATIF TAHUN 2019 DAPIL III DI KOTA BANJAR - purnama, riza; Girsang, Nova Chalimah; Saleh, Rakhmat; Suwangsih, Nunung (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2024)
This research aims to analyze the political marketing strategy applied by the Indonesian Democratic Party of Struggle (PDIP) in the 2019 legislative elections in the Electoral District of Langensari District, Banjar City. (Dapil) III Langensari District, Banjar City. Research method method used is the descriptive method with a qualitative approach. descriptive method with a qualitative approach. The research informants consisted of from PDIP administrators in Dapil III, the success team, and the voters in Langensari Sub-district. in Langensari Subdistrict. The results showed that PDIP managed to utilize the 4P concept effectively in their campaign. The political products offered, in the form of programs and policies, succeeded in attracting voters' interest. Promotions carried out through mass media, social media, and direct campaigns were able to increase awareness and support for PDIP. campaigns were able to increase awareness and support for the party. Price in this context is interpreted as the party's efforts to reduce the cost for voters to support and vote for PDIP. The conclusion of this research is that the implementation of the 4P strategy in political marketing by PDIP in Dapil III Langensari Sub-district, Banjar City made a significant contribution to the party's victory in the 2019 legislative elections.